Acute psychological benefits of exercise: Reconsideration of the placebo effect. (2013) - Szabo, Attila
Abstract : Background: The psychological benefits of exercise are repeatedly and consistently reported in the literature. Various forms of exercise, varying in duration and intensity, yield comparably positive changes in affect, which sheds doubt on the significance of exercise characteristics in the acute mental health benefits resulting from physical activity. Aims: Based on research evidence, it is argued that the placebo effect may play a key role in the subjective exercise experience. This report is aimed at highlighting those aspects of the extant literature that call for the reconsideration of the placebo effect in the understanding of the acute mental benefits of physical activity. Method and results: This narrative review focuses on research evidence demonstrating that the duration and intensity of physical activity are not mediatory factors in the mental health benefits of acute exercise. Current research evidence pointing to the roles of expectancy and conditioning in the affective benefits of exercise calls for the reconsideration of the placebo effect. Conclusion: The present evaluation concludes that new research effort ought to be invested in the placebo-driven affective beneficence of exercise.